A caracterização e correção da deficiência de ferro em plantas de morangueiro: novas abordagens - Pestana, Maribela (2013)
Iron (Fe) is abundant in soils and although it is required in small amounts by plants the incidence of iron chlorosis (Fe deficiency) is very common in a number of crops and requires massive soil application of Fe-chelates to correct it. In this work, we present the most important results obtained in several experiments conducted with strawberry to study the physiological and biochemical response mechanisms to Fe deficiency, and the assessment of novel alternatives to control this nutritional disorder. In all experiments, conducted in hydroponic systems, symptoms were induced by withdrawing Fe from the solution and the results were compared to a control treatment grown with Fe. The degree of chlorosis and symptoms recovery was estimated using SPAD values. The activity of iron chelate reductase, the enzyme responsible for Fe reduction in roots, was determined in root apices by colorimetric quantification of the BPDS complex. The Fe concentration in leaves and roots was quantified by atomic absorption spectrophotometry after treatments at 450 ºC and acid digestion of the ashes obtained. Strawberry plants that grew always without Fe, presented Fe chlorosis and morphological external root modifications associated with increases of the activity of the Fe-reductase enzyme. The recovery of chlorotic plants was achieved by application of Fe sulphate either to leaves or to the nutrient solution. In plants recovered by using Fe in the solution, the enzyme maintained a large activity, suggesting a strategy to increase plant Fe pools. As an alternative to synthetic Fe chelates, we also tested a foliar application of a plant extract obtained from fresh grass clippings (national patent PT/103584-2009 of UALG, and international patent PCT/PT2007/000041-2008, UALG and ADPFertilizantes), which was effective in chlorosis recovery after three applications. The results are discussed in order to highlight the practical implications of these responses under a perspective of optimization of crop Fe fertilization